Pengaruh Promosi Penjualan, Keamanan Berbelanja Dan Kepercayaan Konsumen Terhadap Minat Beli Online Produk Fashion Pada Marketplace Shopee (Studi Kasus Mahasiswa Fakultas Ekonomi Prodi Manajemen Universitas Muhammadiyah Jember 2019) - Ariwibowo, Bagus Joni; Izzuddin, Ahmad; Suharto, Akhmad; Suwarto (Universitas Muhammadiyah Metro, 2024)
Advances in internet technology have changed the way businesses operate. Thanks to theInternet, entrepreneurs have unlimited access to information to support their businessoperations. In this context, electronic commerce has evolved into an environment whereadvances in Internet technology can be used to make products and services available to awider market. The Shopee Online Shopping Application is popular and memorable amongonline shopping customers because of its attractive features. This study has the aim ofknowing the effect of advertising, security, and trust on consumer interest in buying fashionproducts at Shopee. The method used is descriptive quantitative. Students enrolled in theFaculty of Economics Management Course in 2019 comprised the research population. Thesample determination adopted the use of target sampling techniques with a total of 74respondents. The study's conclusions demonstrate that advertising, security, and trust have apositive and significant effect on consumer interest in buying fashion products at Shopeemarketplace.